PENERAPAN KOMPOR MINYAK JELANTAH SEBAGAI SUBSTITUSI BAHAN BAKAR PADA INDUSTRI UMKM MAKANAN - Sanjaya, Ari Susandy; Sukmono, Yudi; Sitania, Farida Djumiati; Widada, Dharma; Wijaya, Muhammad Farhanuddin; Khiyarinnisa, Faza (Jurnal AbdiMas Nusa Mandiri, 2025)
In daily life, stoves are essential tools used in cooking. They play an important role in energy use for households and small businesses, especially MSMEs (Micro, Small, and Medium Enterprises). In Samarinda and surrounding areas, food-related MSMEs are growing rapidly, ranging from snacks to trendy beverages. One of the major components of production costs is fuel. The 3-kg LPG cylinder, commonly called the "melon gas," is widely used due to its affordability and availability in urban areas. However, frequent shortages cause price instability and make it unreliable. To address this, a community service program was conducted through education and mentoring on the use of stoves fueled by used cooking oil as an alternative. Emission test results showed that a stove using used cooking oil reached 303°C with O₂ at 11.13%, CO at 9 ppm, and NaO at 16 ppm in 1 minute. In comparison, a gas stove reached 310.2°C with O₂ at 12.28%, CO at 61 ppm, and no NaO detected. These results show that used cooking oil can be a cost-effective alternative for MSMEs. It not only provides a solution to the unstable LPG supply but also helps reduce environmental impact by reusing waste oil from food processing. The used-oil stove has been well received by local entrepreneurs as an affordable and eco-friendly option.